1997
DOI: 10.1111/j.1365-2222.1997.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergy in greenhouse workers: sensitization to Tetranychus urticae

Abstract: TU could be an important occupational allergen in greenhouse workers showing allergic symptomatology. There is no crossreactivity between this mite and the house dust mite D. pteronyssinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The cultivation of greenhouse flowers and/or ornamental plants emerged as a significant risk factor for bronchial asthma in the European Farmers' Study (8), which focused on the prevalence and risk factors for airway obstruction in farmers and agriculture workers (8)(9)(10). Previous work on greenhouse growers has found a high prevalence of respiratory symptoms when compared with control populations (11), and occupational asthma to Tetranychus urticae , a macroscopic mite that may infest a wide range of plants, has been occasionally reported in these growers (12)(13)(14). Such reports, however, have focused on greenhouse workers cultivating vegetables and tomatoes and have included only flower growers cultivat-ing Dianthus caryophyllus.…”
mentioning
confidence: 99%
“…The cultivation of greenhouse flowers and/or ornamental plants emerged as a significant risk factor for bronchial asthma in the European Farmers' Study (8), which focused on the prevalence and risk factors for airway obstruction in farmers and agriculture workers (8)(9)(10). Previous work on greenhouse growers has found a high prevalence of respiratory symptoms when compared with control populations (11), and occupational asthma to Tetranychus urticae , a macroscopic mite that may infest a wide range of plants, has been occasionally reported in these growers (12)(13)(14). Such reports, however, have focused on greenhouse workers cultivating vegetables and tomatoes and have included only flower growers cultivat-ing Dianthus caryophyllus.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] They are classified in the order Prostigmata, family Tetranichidae, subfamily Tetranichynae. The other spider mite, citrus red mite (Panonychus citri), is the most important inhalant allergen related to occupational asthma found in citrus farm farmers.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 All previous TSM-related reports have been confined to occupational exposures. [2][3][4][5][6][7][8] Although house-dust mite (HDM) has been known as the most important allergen in Korea, 11 a recent investigation demonstrated that TSM could be one of the prevalent inhalant allergens in nonfarmers as well as farmers in pear orchards. 12 Skin prick test (SPT) results of adult asthmatic patients complaining of summer-type asthma indicated that TSM was second in prevalence of sensitivity to HDM.…”
Section: Introductionmentioning
confidence: 99%